The Statistical Measurement of Financial Derivatives - Heath, Robert (Washington, D.C. : International Monetary Fund, 1998)
The System of National Accounts 1993 (1993 SNA) provided new standards for the statistical treatment of financial derivatives. Subsequently, financial derivative markets have evolved, and there have been requests from national statisticians for clarification and amplification of the recommendations in the 1993 SNA and the fifth edition of the IMF's Balance of Payments Manual (BPM5). Meeting this need is the main purpose of this working paper. Its recommendations have been widely discussed in international meetings and have been approved by bodies that effect changes in the 1993 SNA and BPM5.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet